Material subtraction study of AISI T-15-HSS by wire cut electrical discharge machining (CNC-wire cut EDM) based on Taguchi grey relational analysis. (24th April 2019) - Chockalingam, K.; Jawahar, N.; Muralidharan, N.; Jeyaraj, K.L.
The wire cut electrical discharge machining is a kind of non-traditional machining process used to machine harder alloys and metals by thermo spark discharge erosion principle. Whereas the machining process the work piece undergoes different thermal cycles, these will affect the performance of the component. The process parameters which have an influence on the machining performance characteristics such as material removal rate (MRR), surface roughness (Ra), spark gap (SG) and dimensional deviation (DD) while processing/slicing of work piece. In the cutting process of high speed steel (AISI T-15), 250 m diameter of brass wire, used for machining the workpiece by CNC wire cut EDM machine. The proposed problem solved by grey relational and statistical analysis like the Taguchi-based design. The developed empirical relation will indicate the relationship between machining performance and the process parameters, which will be useful for both machine manufacturers and the machine users.